The cold-water coral province of the eastern Ligurian Sea (NW Mediterranean Sea): historical and novel evidences - Bo, Marzia; Enrichetti, Francesco; Betti, Federico; Gay, Guido; Quarta, Gianluca; Calcagnile, Lucio; Bavestrello, Giorgio (Frontiers in Marine Science, 2023)
Several bathyal cold-water coral provinces, characterized by a lush growth of habitat-forming scleractinians, have been recognized in the Mediterranean Sea. However, the search for this biogenic habitat only marginally targeted the Italian coast of the Ligurian Sea (NW Mediterranean basin) despite historical and a few recent local studies in the region reporting the presence of corals. This study used bathymetry maps, side-scan sonar profiles, historical charts, and trawling routes to identify sites that could potentially host coral habitats in the eastern sector of the Ligurian Sea. Remotely operated vehicle video footage from various projects (2015-2021, 20 dives) was then used to characterize four sub-areas (Genoa Plateau, Portofino, Deiva Marina, and Monterosso) where corals were detected between 450 m and 750 m depth. Radiocarbon dating was used to trace back the geological history of the coral structures. A small coral mound, impacted by trawling activities, was found on the Genoa Plateau, while four massive coral structures were found in the other sub-areas, mainly located in a morphologically complex and highly energetic canyon region. High levels of megafaunal biodiversity, including rarely reported alcyonaceans as Placogorgia coronata, were observed together with moderate fishing impact. Overall, the identified coral areas potentially account for 9 km2 of both subfossil mounds (as old as 13300 years BP), dominated by Desmophyllum pertusum, and living reefs, dominated by Madrepora oculata, the latter representing up to 23% of the substrate coverage. The few living colonies of D. pertusum in the area represent the first documented records for the Ligurian Sea. These data support the presence of a distinct eastern Ligurian cold-water coral province.